Effect of heavy metals on kidney function among petroleum industry workers in the Kurdistan region - Hussein S. Husseiny (Zanco Journal of Pure and Applied Sciences, 2023)
Heavy metals have severely polluted the environment. The kidney is usually the first organ to be impacted by heavy metal exposure due to its potential to accumulate and detoxify metal ions. Some heavy metals and kidney function of oil field employees in Kurdistan Region of Iraq were studied in this research. This study was based on primary data collected throughout recent five years. Forty adult males who participated in this region were divided into two main groups; the former consisted of twenty individuals who had been exposed to Occupational Chemicals for more than five years in the oilfield area, and the other included twenty individuals who had not been exposed and used as a control group. Cobas C311 instrument was used as a biochemical analyzer to investigate some biochemical parameters in the serum level, and inductively coupled plasma was performed to estimate some heavy metals in whole blood. The results show a highly significant difference in some heavy metals such as (Silver (Ag), Iron (Fe), Cadmium (Cd), Manganese (Mn) and Vanadium (V)) which increased in the exposed group compared to the group that served as a control. However, there was no statistically significant difference in the levels of the other heavy metals (Mercury (Hg), Lead (Pb), and Zinc (Zn)) between the two groups described. Furthermore, the level of kidney function parameters, including creatinine and blood urea, was revealed non-significantly higher than in the exposed group compared to the control group, except for uric acid, which significantly rose.